2016
DOI: 10.1039/c5nr06098b
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Raman scattering and lattice dynamics in mono- and few-layer WTe2

Abstract: Tungsten ditelluride (WTe2) is a layered material that exhibits excellent magnetoresistance and thermoelectric behaviors, which are deeply related with its distorted orthorhombic phase that may critically affect the lattice dynamics of this material. Here, we report comprehensive characterization of Raman spectra of WTe2 from bulk to monolayer using experimental and computational methods. We find that mono and bi-layer WTe2 are easily identified by Raman spectroscopy since two or one Raman modes that are obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
97
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 50 publications
22
97
2
Order By: Relevance
“…Using the same approach, we also studied the evolution of the Raman-active phonon modes as a function of layer number. We find that the A19 should redshift from 211.36 cm −1 for monolayer material to 209.53 cm −1 for bulk, in agreement with our measurements and previous DFT studies [21, 31]. …”
Section: Characterization Of Monolayer 1t’-wte2 Flakessupporting
confidence: 93%
See 2 more Smart Citations
“…Using the same approach, we also studied the evolution of the Raman-active phonon modes as a function of layer number. We find that the A19 should redshift from 211.36 cm −1 for monolayer material to 209.53 cm −1 for bulk, in agreement with our measurements and previous DFT studies [21, 31]. …”
Section: Characterization Of Monolayer 1t’-wte2 Flakessupporting
confidence: 93%
“…The flake was encapsulated with large-area graphene to avoid degradation during the measurements. Two main Raman peaks were observed: the in-plane A17 peak, and the A19 peak, which contains both in-plane and out-of-plane vibrations [21]. For the monolayer region, the A17 and A19 peaks were observed at 163.2 cm −1 and 214.7 cm −1 , respectively.…”
Section: Characterization Of Monolayer 1t’-wte2 Flakesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 59 ] It was also shown that WTe 2 with more than six layers exhibits almost the same Raman frequencies as those in bulk WTe 2 , which are 118, 134, 164, and 212 cm −1 , respectively. [ 59 ] It was also shown that WTe 2 with more than six layers exhibits almost the same Raman frequencies as those in bulk WTe 2 , which are 118, 134, 164, and 212 cm −1 , respectively.…”
Section: Preparation Of Wte 2 Microfl Akesmentioning
confidence: 84%
“…This novel scenario promises an abundance of unexplored experimental possibilities, such as the observation of magnetic breakdown in transport experiments [33]. Our theory and tight-binding models should serve as important resources for ongoing experimental efforts [34,35] focused on the synthesis and the study of MTe 2 monolayers.…”
Section: Introductionmentioning
confidence: 99%